The pK value of ligands and stability constants of the complexes of Fe(III), Cu(II) Ni(II) with some hydroxamic acids: a comparative study of three diifferent potentiometric methods - Senthilnithy, R.; Costa, M.D.P. De; Gunawardhana, H.D. (My University, 2008)
The determination of ionization constants and the chelating properties exhibited by a series of derivatives of N-phenylbenzohydroxamic acid, N-phenyllaurohydroxamic acid and 1-naphmalenememylimminodiacetohydroxamic acid type ligands toward Fe(III), Cu(II) and Ni(II) ions were studied by pH-metric method. The data obtained by pH-metric method were analyzed by three standard methods namely, Bjerrum's method, Irving and Rossotti method, and Sarkar and Kruck method. The ionization constants of hydroxamic acids and the stability constants of metal-ligand complexes were calculated using the above three methods and it was found that the values obtained closely agreed with each other. The evaluation of the calculated stability constants shows that the substituent effect on the N-phenyl ring leads to more basic character at the carbonyl oxygen and it influences significantly the stability of the complex species formed by the hydroxamate moieties. The stability constant and the species distribution of Fe(III) - 1-naphmalenemethylimminodiacetohydroxamic acid system at physiological pH range (6.8 - 7.2) suggest that 1-naphmalenememylimminodiacetohydroxamic acid is an effective source for the iron overload.
Keywords: Bjerrum methods; Hydroxamic acid; Irving and Rossotti method; Sarkar and Kruck method